Impact of overconfidence, optimism, pessimism and herd mentality on trading volume in Vietnam’s stock market - Xuan, Phan Ngoc Yen; Van, Pham Thanh (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the impact of overconfidence, optimism, pessimism, and herd mentality on trading volume in the Vietnamese stock market. Using daily VN30 index price and trading volume data from January 1, 2020, to June 30, 2024, the study employs Wavelet Transform, Spillover Index, and Spectral Granger Causality tests to explore the dynamic relationships between investor sentiment and trading activity. The results reveal that overconfidence has a relatively minor impact, whereas optimism significantly increases trading activity during bull markets. In contrast, pessimism and herd mentality strongly influence trading volume across all market conditions. Optimism amplifies herd behavior, fostering investor confidence, while pessimism weakens market stability by transmitting negative sentiment signals. These findings highlight the importance of incorporating psychological factors into market analysis to enhance predictive accuracy. Understanding these behavioral influences enables investors and policymakers to develop strategies that mitigate sentiment-driven volatility, promote rational investment decisions, and improve financial market stability.